2022
DOI: 10.1590/1809-2950/22005029022022en
|View full text |Cite
|
Sign up to set email alerts
|

Physical capacity assessment in patients hospitalized with COVID-19 diagnose

Abstract: SARS-CoV-2 infection can cause severe acute respiratory syndrome (SARS), leading to hypoxemia. Physical capacity assessment can be performed before hospital discharge using submaximal exercise testing. This study sought to assess physical capacity and exercise tolerance with the six-minute step test (6MST) in hospitalized COVID-19 patients who required oxygen (O2) support during hospitalization. A prospective, interventional study was conducted with patients aged from 18 to 90 years who required oxygen therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…Similar results were found in two previous studies that performed the 6MST on severe COVID-19 patients. The first study was conducted by Lydia J. et al who found decreased climbed steps with an average of 86 ± 39 steps [20] and the second study was by Bianca Setra et al who also found a low performance of the 6MST with an average of 92.3 climbed steps [21]. However, both authors assessed severe cases of COVID-19 survivors, thus explaining the less average number of steps in their results compared to our result.…”
Section: Discussioncontrasting
confidence: 53%
“…Similar results were found in two previous studies that performed the 6MST on severe COVID-19 patients. The first study was conducted by Lydia J. et al who found decreased climbed steps with an average of 86 ± 39 steps [20] and the second study was by Bianca Setra et al who also found a low performance of the 6MST with an average of 92.3 climbed steps [21]. However, both authors assessed severe cases of COVID-19 survivors, thus explaining the less average number of steps in their results compared to our result.…”
Section: Discussioncontrasting
confidence: 53%